Official communication of the SSC: Recommendations for future research in catheter‐related arterial thrombosis in children. Issue 2 (15th January 2019) - Albisetti, Manuela; Rizzi, Mattia; Bonduel, Mariana; Revel‐Vilk, Shoshana; Goldenberg, Neil
Abstract: Catheter‐related arterial thrombosis (CAT) are increasingly recognized in infants and children. Insufficient data are available on the incidence, risk factors, treatment and outcome of these thrombotic events. This work provides consensus recommendations for future research on catheter‐related arterial thrombosis in the paediatric population. In particular, future studies should distinguish between CAT due to indwelling arterial catheters or cardiac catheterization in two different subpopulations (neonates and older children). Further studies should investigate sensitivity and specificity of clinical signs and symptoms for early screening of CAT and the most appropriate imaging modality, focusing on ultrasound due to better feasibility in the very young pediatric population. Adequately powered, well‐designed clinical trials should investigate efficacy and safety of different treatment and prevention strategies as well as the risk for and the optimal management of short‐ and long‐term complications.